Thermal Analysis of Asphalt Concrete Pavements Heated with Amorphous Metal Technology. (13th December 2018) - Sangiorgi, Cesare; Settimi, Cecilia; Tataranni, Piergiorgio; Lantieri, Claudio; Adomako, Solomon
Abstract : Undoubtedly, the most commonly used method for road maintenance includes the use of winter service vehicles to clear thoroughfares of snow and the spraying of chemicals to prevent ice formation on the road surface. The application of these traditional methods on road and airport pavements possesses numerous environmental, organizational, and technical challenges. To overcome these critical issues, new nontraditional technologies that act within the pavement, thereby increasing its temperature, have been developed. In relation to the heat source used, these are classified into chemical and physical methods. The purpose of this research is to study the temperature variation under the thermal transient process produced by the action of the physically heating device installed in the road pavement. The heating device is a ribbon, made of amorphous material, which is able to produce heat to warm up the pavement and its surface. Based on its principle of operation, it is classified among the nontraditional physical methods for the treatment of snow and ice. In this work, the performance of the heating ribbons on an experimental site at the G. Marconi International Airport in Bologna (Italy) is presented.